12. On the nomenclature of the western Orocantabrian evergreen-oak forests - Izco, Jesús; Fernández-González, Federico (Lazaroa, 2014)
The syntaxonomical separation of two associations of evergreen-oak forests in the Cantabrian mountain range (Orocantabrian and Cantabrian-Atlantic biogeographical Provinces) has recently been contemplated.